Development of STEM-based worksheets on recycled plastic panels to enhance student creativity - Yaumil Akmalya Harahap; M. Adlim; M. Hasan; S. Susilawati; Muhammad Zulfajri; H. Habibati (Universitas Muhammadiyah Malang, 2025)
Plastic waste has been the global environmental issue because of its non-biodegradable material and detrimental impact on ecosystems. Addressing this issue requires innovative educational strategies that not only convey knowledge but also foster environmental awareness and creative thinking. This study aims to develop a STEM-based student worksheet on recycled plastic panels to enhance students’ creativity. The worksheet integrates plastic recycling into functional product design through project-based learning. Employing the ADDIE development model, the study involved 124 senior high school students across four classes using a quasi-experimental pretest-posttest control group design. A creativity test was used as the research instrument, measuring fluency, flexibility, and originality. Data analysis confirmed normal distribution (p > 0.05) and significant differences between pretest and posttest scores (p < 0.0001). All creativity indicators improved, with average N-gain scores of 0.70 (high) and 0.62 (moderate). These results indicate that STEM-based worksheets effectively promote student creativity in solving real-world environmental problems, particularly in the context of plastic waste.